Immune Responses to Lentiviral Vectors - Follenzi, Antonia; Santambrogio, Laura; Annoni, Andrea (Current Gene Therapy, 2007)
Efficient delivery and sustained expression of a therapeutic gene into human tissues are the requisite to accomplish the high expectations of gene therapy. A major challenge has concerned development of gene transfer systems capable of efficient cell transduction and transgene expression without harm to the recipient. A lot of work has been done to demonstrate the efficacy of gene therapy in animal models that mimic situations in humans. Use of lentiviral vectors (LVs) offers multiple advantages for gene replacement therapy, because they combine efficient delivery, ability to transduce proliferating and resting cells, capacity to integrate into the host chromatin to provide stable long-term expression of the transgene, absence of any viral genes in the vector and absence of interference from preexisting viral immunity. However, one of the major barriers to stable gene transfer by LVs and other viral vectors is the development of innate and adaptive immune responses to the delivery vector and the transferred therapeutic transgene. Since this greatly hinders the therapeutical benefits of gene therapy by LVs, developing strategies to overcome the host immune response to the transfer vector and the transgene is a matter of current investigation.
Keywords: innate immunity